2005
DOI: 10.1111/j.1600-051x.2005.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein‐associated phospholipase A2 and plasma lipids in patients with destructive periodontal disease

Abstract: This study indicates that treatment of periodontitis significantly reduces the serum activity of Lp-PLA(2), which is believed to be an independent cardiovascular risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 40 publications
4
61
0
1
Order By: Relevance
“…Montebugnoli et al (2005) showed a mean reduction in ox-LDL of 18% in patients affected by periodontitis and CHD, whilst Tamaki et al (2011) demonstrated a 37% reduction following periodontal therapy in otherwise healthy patients. In addition, Losche et al (2005) found that the treatment of periodontitis could influence the serum activity of Lp-PLA2.…”
Section: Periodontal Treatment and Cvd Outcomes S87mentioning
confidence: 99%
“…Montebugnoli et al (2005) showed a mean reduction in ox-LDL of 18% in patients affected by periodontitis and CHD, whilst Tamaki et al (2011) demonstrated a 37% reduction following periodontal therapy in otherwise healthy patients. In addition, Losche et al (2005) found that the treatment of periodontitis could influence the serum activity of Lp-PLA2.…”
Section: Periodontal Treatment and Cvd Outcomes S87mentioning
confidence: 99%
“…Recent studies illustrate the existence of a relation between periodontal disorders and hyperlipidemia, which power the probable effect of periodontal disease as an underlying factor for hyperlipidemia. This theory is presented in Losche et al study, which demonstrated higher level of TGL and lower HDL among the patients suffering from periodontitis than control group significantly, 12 which was approved by some other studies. [13][14][15] The aim of the present study was to investigate the effect of nonsurgical periodontal therapy (NSPT) on the lipid levels in patients with chronic periodontitis.…”
Section: Introductionmentioning
confidence: 79%
“…TC and LDL as well as TG in patients with severe periodontitis. 12,34 However, further investigations are needed for further exploration of the relationship among periodontitis, periodontal therapy and lipid metabolism. Larger studies and clinical intervention trials are necessary to better define the periodontitis subjects in whom local infection causes significant systemic inflammation, and whether these findings are true or are confounded by other important factors like nutrition, socioeconomic status, or age.…”
Section: Jaypeementioning
confidence: 99%
See 1 more Smart Citation
“…It should be highlighted that recent cross-sectional studies, which investigated the relationship between periodontal disease and serum lipid have obtained similar findings to the present study. 32,33 Previous study reported that chronic inflammation in periodontal tissue significantly correlated with TC and LDL, while it showed no relationship with TG and HDL. Greater loss of attachment >3 mm was reported previously to have 1.31 times greater in intima-media wall thickness as pre-atherosclerotic condition.…”
Section: Discussionmentioning
confidence: 99%